Lesson study in initial teacher education : principles and practices - Wood, Phil; Lynn Sorton Larssen, Deborah; Cajkler, Wasyl; Helgevold, Nina (Emerald Publishing Limited, 2019)
This book explores the use of lesson study within the context of initial teacher education. The lesson study process is broken down into its main components and these elements are discussed with references to the specific needs of practitioners, educators and researchers in initiating and developing lesson study in teacher education.Lesson Study in Initial Teacher Education highlights the importance of embedding lesson study within initial teacher education programmes, including building partnerships, making time to carry out collaborative inquiries using lesson study, and frameworks for reporting on lesson study projects. Written by a group of researcher practitioners with extensive experience in developing and managing lesson study in initial teacher education programmes, this book presents a critical overview of the principles and practices at the core of developing collaborative inquiry amongst those being educated to become teachers. By outlining an innovative framework to support professional learning classroom-based research, this book will prove invaluable for researchers, administrators and leaders in teacher education.